Microbiomorphic analysis as part of micromorphological investigations: composition, diagnostics and informative capacity for paleoenvironmental reconstructions - A. A. Golyeva (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
Microbiomorphic analysis is a detailed study of microscopic particles of biogenic nature (plant detritus, phytoliths, shells of diatoms, spicules of sponges, pollen, etc.). Each of such particles characterizes environmental conditions at the time of its formation and, therefore, provides useful information for palaeoenvironmental reconstructions. The Early Pleistocene deposits were studied in Armenia at the sites, where tools of ancient hominids (Early Acheulian) were found. The genesis of these deposits was identified. It was shown that these ancient alluvial-lacustrine sediments were transformed by soil-forming processes. The environmental conditions at the time of the ancient hominids’ migration were reconstructed.